AB0800 CLINICAL ASSOCIATION BETWEEN URIC ACID/25-HYDROXYVITAMIN D SERUM LEVELS RATIO IN PATIENTS WITH PSORIATIC ARTHRITIS. (2nd June 2020) - Masini, F.; Gjeloshi, K.; Pinotti, E.; Danzo, F.; Guarino, F.; Tardugno, M.; Ferrara, R.; Cuomo, G.
Abstract : Background: The association between hyperuricemia and psoriatic arthritis (PsA) is actually generally accepted. Previous studies have demonstrated that uric acid suppress 25(OH)D metabolism [1]. More evidence is required to demonstrate the immune modulatory effects in psoriasis, psoriatic arthritis and other autoimmune diseases. In particular, the potential association between 25-hydroxyvitamin D serum levels and PsA still remains unknown. Objectives: To assess a clinical association between uric acid/25(OH)D serum levels ratio related to PASI, BASDAI and DAPSA, if any, in patients with psoriatic arthritis. Methods: We retrospectively observed 61 patients with psoriatic arthritis referred to our outpatients clinic, independently from already being on therapy or naïve. All selected patients underwent only conventional non-biological therapy at baseline and none received vitamin D supplementation and either allopurinol or febuxostat previously. Blood samples were drawn from all participants for assessment of 25-hydroxyvitamin D and uric acid serum levels. Disease activity of psoriasis and psoriatic arthritis were assessed by the Psoriasis Area and Severity Index (PASI), the Disease Activity Index for Psoriatic Arthritis (DAPSA) and the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI). We assessed the covariates of interest by the Wilcoxon non parametric test, through the SPSS 24 Software. Results: We observed 61 patients, mainly females (83.6%). At the univariate analysis, the uric acid/25(OH)D serum levels ratio revealed significantly associated with DAPSA and BASDAI indexes (p<0.001 and p<0.001, respectively), whilst no significant association emerged with the PASI index (p=0.462). Conclusion: Data in the literature about these associations in the context of psoriatic arthritis are really poor. As a consequence, our findings, though preliminary, suggest us to hypothesize a potential role of uric acid/25(OH)D serum levels ratio as potential inflammation marker in order to better assess the disease activity. However, future larger studies are needed to investigate more in depth this association. [1]Charoenngam N, Ponvilawan B, Ungprasert P. Vitamin D insufficiency and deficiency are associated with a higher level of serum uric acid: A systematic review and meta-analysis. Mod Rheumatol. 2019 Mar 4:1-6. Disclosure of Interests: None declared